2022
DOI: 10.55493/5007.v12i5.4486
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the Remittance Inflows in Bangladesh: An ARDL Approach

Abstract: The key concern of this paper is to bring forth a contemporary estimation of the impact of the ongoing COVID-19 pandemic on remittance inflows in Bangladesh as well as to find out the scenario of whether the migration and exchange rate have impacted on the remittance inflows in Bangladesh based on the monthly data from January 2008 to December 2021. By introducing dummy variable in the Autoregressive Distributed Lag (ARDL) bound testing approach, it is found that the ongoing COVID-19 pandemic has a strong posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…They predicted that countries with less diversified labor destinations would be hit more severely due to the temporary suspension of labor migration. Akter et al (2022) analyzed monthly remittance data of Bangladesh from January 2008 to December 2021 and applied the autoregressive distributive lag (ARDL) estimation technique. They revealed that remittance inflow increased during the pandemic, supporting the "Altruistic" motive.…”
Section: Covid-19 and Its Impact On Remittance Inflowmentioning
confidence: 99%
“…They predicted that countries with less diversified labor destinations would be hit more severely due to the temporary suspension of labor migration. Akter et al (2022) analyzed monthly remittance data of Bangladesh from January 2008 to December 2021 and applied the autoregressive distributive lag (ARDL) estimation technique. They revealed that remittance inflow increased during the pandemic, supporting the "Altruistic" motive.…”
Section: Covid-19 and Its Impact On Remittance Inflowmentioning
confidence: 99%